Teachers’ Perceptions of Creativity Across Cultures: A Systematic Literature Review - Smare, Zaina (Creativity : theories - research - applications, 2025)
Creativity has been identified as one of the top three most essential skills of the 21st century. The ability to think creatively is of paramount importance in all countries and nations. However, not every culture perceives creativity and creative people in the same way. Investigating cultural variations in relation to creativity can help clarify the nature of the concept. The resulting insight can then inform the development of more appropriate educational approaches that promote this skill. It is well documented that teachers are important gatekeepers in the development of students’ creative potentials. That is why, this article aims to examine how cultural values influence teachers’ perceptions of creativity across various cultural contexts, with a specific focus on comparing perceptions between individualistic and communitarian cultures. To achieve this aim, we systematically surveyed the literature and analyzed 47 empirical studies conducted in a wide range of cultural contexts between the years 2010 and 2024. The findings revealed that individualistic cultures relate creativity to originality, independence, risk taking, and freedom, while communitarian cultures tend to focus on the appropriateness of ideas, cooperation among students, and respect of the social norms. Implications of these findings for education and suggestions for further research are discussed.